2018
DOI: 10.30852/sb.2018.499
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impact on groundwater recharge and suggested adaptation strategies for selected Asian cities

Abstract: Climate change impact on groundwater recharge and suggested adaptation strategies for selected Asian citiesCurrently, 54% of the world's population live in urban areas, and this figure is expected to increase to 66% by 2050. Major cities and municipalities in the region rely either wholly or partially on groundwater. Four Asian cities, namely Bangkok, Bandung, Ho Chi Minh City, and Lahore, are selected for the study as their groundwater dependency is in the critical range of 45% to 100%. Therefore, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Globally, two modelling studies have shown substantial decreases in groundwater in regions including the Mediterranean, north-eastern Brazil and south-western Africa, with less clarity for other regions (Döll, 2009;Portmann et al, 2013). Recent regional-scale analyses of the impact of water cycle changes on groundwater recharge (e.g., Meixner et al, 2016;Tillman et al, 2017;Shrestha et al, 2018) suggest changes in both seasonality and spatial distribution, which are amplified under a higher greenhouse-gas emissions scenario (i.e., RCP 8.5 compared to RCP4.5). Seasonality changes are linked to increases during wet winter periods and declines during dry summer periods.…”
Section: Groundwatermentioning
confidence: 99%
“…Globally, two modelling studies have shown substantial decreases in groundwater in regions including the Mediterranean, north-eastern Brazil and south-western Africa, with less clarity for other regions (Döll, 2009;Portmann et al, 2013). Recent regional-scale analyses of the impact of water cycle changes on groundwater recharge (e.g., Meixner et al, 2016;Tillman et al, 2017;Shrestha et al, 2018) suggest changes in both seasonality and spatial distribution, which are amplified under a higher greenhouse-gas emissions scenario (i.e., RCP 8.5 compared to RCP4.5). Seasonality changes are linked to increases during wet winter periods and declines during dry summer periods.…”
Section: Groundwatermentioning
confidence: 99%
“…Groundwater availability is not enough to meet the growing demand, leading to overexploitation and depletion of groundwater resources. In particular, South Asia is facing alarming groundwater depletion, with an annual depletion rate of 60 Billion Cubic Meters (BCM) and an increase in air temperature and evapotranspiration [1]. Additionally, Groundwater quality is continuously changing due to climatic change and human activities, emphasizing the need for comprehensive understanding and assessment of climate change impacts on water resources [2,33,34].…”
Section: Impact Of Climate Change On Groundwatermentioning
confidence: 99%
“…Additionally, Groundwater quality is continuously changing due to climatic change and human activities, emphasizing the need for comprehensive understanding and assessment of climate change impacts on water resources [2,33,34]. It also has the potential to contribute to climate change mitigation through geothermal energy use and CO2 capture and storage [1,3].…”
Section: Impact Of Climate Change On Groundwatermentioning
confidence: 99%
“…Increasing droughts will cause stress to coastal and inland wetlands. Groundwater recharge is expected to respond to climate change with increases during wet, winter periods and declines during dry, summer periods; overall declines are expected in more arid locations (72). Higher temperature increases result in higher projected numbers of people exposed to, and vulnerable to, water scarcity and droughts (70,71).…”
Section: Droughtmentioning
confidence: 99%